Technopreneurial Language Development Strategies for Children with ADHD - Yulianti, Uki Hares; Zulaeha, Ida; Subyantoro, Subyantoro; Nugroho, Yusro Edi; Versie, Ikyboy Van (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study explores the characteristics of speech disorders in children with ADHD and examines effective intervention strategies, including technopreneurial solutions, and parental language practices to support their communication development. The research aims to bridge the gap in current intervention models by integrating traditional speech therapy with innovative, technology-driven approaches, such as AI-powered diagnostic tools and digital platforms. Using a qualitative case study method, data were collected through structured clinical observations, speech sample analysis, and in-depth interviews with pediatricians, child psychologists, speech therapists, and parents of children with varying types of ADHD. The results reveal that children with ADHD commonly experience articulation difficulties, disfluency, and impairments in receptive, expressive, and pragmatic language skills. A novelty of this study is the development of a structured intervention model that combines conventional speech therapy with ADHD-sensitive techniques, including behaviour management, visual aids, and environmental adaptations, alongside AI-driven diagnostic tools and digital platforms to enhance accessibility and engagement. Additionally, a practical guide to language parenting was designed to empower parents and caregivers to actively support therapy outcomes by using consistent communication strategies at home. The study also produced a comprehensive database of speech characteristics in Indonesian children with ADHD, serving as a foundation for further research and development of more effective assessment instruments. This research underscores the importance of multidisciplinary collaboration and parental involvement in addressing speech disorders in children with ADHD, aligning with SDGs 3 (Good Health and Well-being) and SDGs 4 (Quality Education).